PENGARUH LEVERAGE, INFLASI, DAN PDB PADA HARGA SAHAM PERUSAHAAN ASURANSI - Adi Putra, Gede Sanjaya; Yaniartha, Putu Dyan (E-Jurnal Akuntansi, 2014)
This study aims to determine the effect of the leverage ratio, inflation rate, and the growth of GDP in stock prices of insurance companies listed on the Stock Exchange. this study used a quantitative approach to research methods in the form of associative with the type of causality. the authors conducted a data collection technique using nonparticipant observation, documentation methods, and metose literature. The population used 15 firms.   the sample number of 12 companies. Based on the analysis conducted revealed that the DER and inflation has no effect on the value of the insurance company's shares listed on the Stock Exchange. However, on the other hand the growth of GDP in the same direction and significant impact on the value of the insurance company's shares listed on the Stock Exchange.
Keywords: leverage: inflation: gross domestic product